Process for the production of light, highly dispersed modified high-purity calcium oxide

CN120463222BActive Publication Date: 2026-10-13CHANGSHU HONGYU CALCIFICATION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510524111.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-13
Estimated Expiration
2045-04-24

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了轻质高分散改性高纯氧化钙工艺,解决了现有高纯氧化钙制备工艺中轻质化、分散性、纯度与环保性难以兼容的共性技术瓶颈的问题

Benefits of technology

[0033]1、本发明通过分阶段控温策略结合纳米纤维素的自牺牲特性,在钙源分解前优先建立三维贯通孔隙框架,同步实现轻质化与高比表面积。相较于传统一步煅烧工艺中模板分解与成晶相互干扰的缺陷,该方案突破了孔隙率与晶粒完整性难以共存的矛盾,使氧化钙在微观结构上兼具低密度与高活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120463222B_ABST
    Figure CN120463222B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of calcium oxide preparation, and discloses a light high-dispersion modified high-purity calcium oxide process, which comprises the following steps: S1, precursor preparation: mixing a calcium source, a biological template and a dispersing agent to form a sol, and obtaining liquid drops through aerosol atomization; S2, template self-assembly: low-temperature drying the liquid drops, so that the biological template and the calcium source are self-assembled to form a three-dimensional network structure; S3, gradient calcination: stage-by-stage temperature control calcination, the biological template is decomposed to generate pores in the first stage, and the calcium source is decomposed to generate calcium oxide in the second stage; S4, in-situ passivation: passing in a passivator vapor at the end of the calcination to modify the surface of the calcium oxide; and S5, cooling and packaging: cooling and vacuum packaging under an inert atmosphere. Through the stage-by-stage temperature control strategy and the self-sacrifice characteristics of nanocellulose, a three-dimensional through-pore framework is preferentially established before the calcium source is decomposed, and lightness and high specific surface area are simultaneously realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of calcium oxide preparation technology, specifically to a process for producing lightweight, highly dispersed, modified high-purity calcium oxide. Background Technology

[0002] High-purity calcium oxide, due to its high thermal stability and chemical activity, has important applications in environmental adsorption, fine chemicals, and new energy materials. However, existing preparation technologies generally face bottlenecks in synergistically improving lightweight properties, high dispersibility, and purity. While traditional high-temperature solid-state methods (>1000℃) can improve purity, excessive grain growth leads to a sharp decrease in specific surface area (typically <10 μm²). 2 / g), and the energy consumption is extremely high; although the liquid phase precipitation method can refine the particles, the capillary force effect during the precursor drying process causes hard agglomeration, which requires subsequent grinding and dispersion, thus introducing impurities.

[0003] To improve pore structure, existing technologies often employ template methods (such as polystyrene microspheres, starch, etc.) to assist in pore formation. However, these templates tend to leave carbonaceous residues (>0.5wt%) after pyrolysis, requiring secondary acid washing for removal. This not only increases the number of steps but also causes pore wall collapse and a decrease in purity (<99%). Furthermore, the physical mixing of the template agent and the calcium source makes it difficult to avoid component segregation, leading to pore blockage or poor permeability in the calcined product, resulting in actual adsorption performance far below the theoretical value.

[0004] Regarding dispersion control, conventional processes rely on wet coating (such as silane coupling agents) or surfactant modification, but post-processing steps easily introduce organic residues, and the coating layer is prone to decomposition and failure during high-temperature service. More critically, the existing passivation process is implemented separately from the calcination process, resulting in weak adhesion between the passivation layer and the substrate, which cannot suppress the volume expansion and pulverization caused by calcium oxide's moisture absorption, severely restricting its long-term storage stability. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a process for modifying high-purity calcium oxide with lightweight and highly dispersed properties, which solves the common technical bottleneck problem in the preparation of high-purity calcium oxide where it is difficult to reconcile lightweighting, dispersibility, purity, and environmental friendliness.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a process for modifying high-purity calcium oxide with light and highly dispersed materials, comprising the following steps:

[0007] S1. Precursor preparation: Calcium source, biological template and dispersant are mixed to form a sol, which is then atomized into droplets by aerosol;

[0008] S2, Template self-assembly: The droplets are dried at low temperature, allowing the biological template and calcium source to assemble into a three-dimensional network structure;

[0009] S3, gradient calcination: staged temperature-controlled calcination, the first stage decomposes the biological template to generate pores, the second stage decomposes the calcium source to generate calcium oxide;

[0010] S4. In-situ passivation: Passivating agent vapor is introduced at the end of the calcination stage to modify the surface of calcium oxide;

[0011] S5. Cooling and Packaging: Cooled under an inert atmosphere and vacuum-sealed.

[0012] Preferably, in step S1:

[0013] The droplet diameter of aerosol atomization is 10–50 μm;

[0014] The biological template is cellulose nanofiber, and the amount added is 5-10 wt% of the dry weight of the calcium source.

[0015] The dispersant is citric acid, and the amount added is 0.05 to 0.1 wt% of the dry weight of the calcium source.

[0016] Preferably, in step S2:

[0017] The low-temperature drying temperature is 60±2℃, the drying atmosphere is nitrogen, and the flow rate is 1~2L / min;

[0018] The self-assembly is achieved through hydrogen bonding, forming through-pores with a diameter of 1–5 μm.

[0019] Preferably, in step S3:

[0020] The first stage of calcination is at a temperature of 200–400℃, with a heating rate of 1–2℃ / min, and is held for 1–2 hours.

[0021] The second stage of calcination is carried out at a temperature of 500–700℃, with a heating rate of 10–15℃ / min and a holding time of 0.5–1 hour.

[0022] Preferably, the second stage of calcination is carried out under a nitrogen atmosphere with a gas flow rate of 5-8 L / min.

[0023] Preferably, in step S4:

[0024] The passivating agent is ethanol vapor with a concentration of 0.3–0.7 vol%.

[0025] The passivation treatment temperature is 650-700℃, and the treatment time is 10-15 minutes.

[0026] Preferably, in step S5:

[0027] Cooling was carried out under a nitrogen atmosphere at a flow rate of 3–5 L / min, with a final cooling temperature of <200℃.

[0028] The vacuum level of the vacuum seal is <100Pa.

[0029] Preferably, the matching relationship between the droplet diameter of 10-50 μm and the amount of biological template added of 5-10 wt% satisfies the following: the ratio of droplet volume to template network volume is 1:0.2-0.5.

[0030] Preferably, the ratio of the heating rate of the first stage calcination (1-2°C / min) to the heating rate of the second stage calcination (10-15°C / min) is 1:5 to 1:10.

[0031] Preferably, the correlation between the ethanol vapor concentration of 0.3 to 0.7 vol% and the passivation temperature of 650 to 700°C satisfies the following condition: for every 0.1 vol% increase in ethanol vapor concentration, the passivation temperature decreases by 10 to 15°C.

[0032] This invention provides a process for modifying high-purity calcium oxide with lightweight and highly dispersed properties. It offers the following advantages:

[0033] 1. This invention utilizes a staged temperature control strategy combined with the self-sacrificing properties of nanocellulose to preferentially establish a three-dimensional interconnected porous framework before the calcium source decomposes, simultaneously achieving lightweighting and high specific surface area. Compared to the defects of template decomposition and crystallization interference in the traditional one-step calcination process, this scheme overcomes the contradiction between porosity and grain integrity, enabling calcium oxide to possess both low density and high activity in its microstructure.

[0034] 2. This invention employs citric acid molecules to bridge calcium source particles with a CNF network, suppressing component segregation through dynamic adsorption equilibrium to form a nanoscale interpenetrating composite precursor. Existing technologies relying on mechanical mixing for homogenization often lead to droplet drying and aggregation, while this approach achieves cross-scale dispersion stability from droplets to the final product through molecular interface engineering, significantly improving the environmental response uniformity of calcium oxide particles.

[0035] 3. This invention introduces ethanol vapor to simultaneously complete surface hydroxylation and passivation at the end of calcination, and utilizes high-temperature gas-solid reaction to construct a chemically bonded protective layer. Traditional post-processing coating processes introduce impurities due to secondary processing and have insufficient coverage. This solution, through in-situ reaction kinetic control, imparts long-lasting moisture-wicking and anti-agglomeration properties to calcium oxide while avoiding the loss of surface active sites. Attached Figure Description

[0036] Figure 1 This is a process flow diagram of the present invention. Detailed Implementation

[0037] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] Example:

[0039] Please see the appendix Figure 1 This invention provides a process for modifying high-purity calcium oxide with light and highly dispersed properties, comprising the following steps:

[0040] S1. Precursor preparation: Calcium source, biological template and dispersant are mixed to form a sol, which is then atomized into droplets by aerosol;

[0041] This step utilizes aerosol atomization technology to transform the calcium source (CaOH)₂, the biological template (cellulose nanofibers, CNF), and a trace amount of citric acid dispersant into uniform micron-sized droplets (10-50 μm). Within the droplets, electrostatic repulsion and steric hindrance maintain the stable dispersion of the nanoparticles, while the CNF acts as a sacrificial template, penetrating throughout the calcium source matrix to form a "calcium source-template" composite precursor. This design, through the synergistic effect of physical confinement and chemical dispersion by aerosols, solves the technical challenges of uneven template distribution and easy sedimentation in traditional wet processes, providing a homogenized foundation for subsequent self-assembly.

[0042] S2, Template self-assembly: The droplets are dried at low temperature, allowing the biological template and calcium source to assemble into a three-dimensional network structure;

[0043] During low-temperature drying (60±2℃), the hydroxyl groups on the CNF surface spontaneously assemble with Ca(OH)2 particles through hydrogen bonding to form a three-dimensional network structure. In this process, slow dehydration under nitrogen protection promotes the formation of a tightly interwoven composite framework between the CNF and the calcium source, while simultaneously reserving pore channels after template pyrolysis. Compared to traditional high-temperature drying, the low-temperature environment effectively inhibits the premature decomposition of the calcium source precursor, preserves active sites, and provides structural guidance for the directional reaction in the subsequent calcination stage. The dynamic and reversible nature of hydrogen-bonded self-assembly allows the CNF to adaptively adjust its network topology during drying, forming a preliminary interconnected pore structure, while avoiding structural collapse caused by high temperatures, achieving a balance between lightweighting and mechanical stability.

[0044] S3, gradient calcination: staged temperature-controlled calcination, the first stage decomposes the biological template to generate pores, the second stage decomposes the calcium source to generate calcium oxide;

[0045] Gradient calcination is divided into two stages:

[0046] First stage (200~400℃): CNF is pyrolyzed under a nitrogen atmosphere to generate CO2 and H2O gas. The gas escapes to form through pores with a diameter of 1~5μm, and the heat released at the same time activates the surface activity of the calcium source.

[0047] The second stage (500–700℃): Ca(OH)₂ rapidly decomposes into CaO. At this stage, the residual gas generated by the template pyrolysis forms a local high-pressure microenvironment, inhibiting the diffusion growth of CaO grains and limiting their size to the range of 20–50 nm. The staged temperature control, through a "pore-forming first, crystallization later" sequential design, utilizes the kinetic effect of gas release to suppress grain coarsening. At the same time, low-temperature calcination (compared to the traditional 1200℃) significantly reduces energy consumption, solving the mutually exclusive problem of high dispersibility and low energy consumption.

[0048] S4. In-situ passivation: Passivating agent vapor is introduced at the end of the calcination stage to modify the surface of calcium oxide;

[0049] At the end of calcination (700℃), a trace amount of ethanol vapor (0.3-0.7 vol%) is introduced. Ethanol molecules react with highly reactive oxygen vacancies on the CaO surface to generate a hydroxylated surface layer (Ca-O-CH2CH3). This passivation layer reduces the surface energy of CaO, preventing premature reaction with H2O or CO2 in the environment, and also avoiding van der Waals aggregation between particles. Compared to traditional post-treatment techniques such as stearic acid coating, in-situ passivation eliminates the need to introduce foreign organic matter, and significantly improves the gas-solid reaction efficiency at high temperatures. The pyrolysis-adsorption-recombination process of ethanol vapor at high temperatures achieves chemical bonding between the passivation layer and the CaO matrix, rather than physical adsorption, thereby optimizing surface stability and dispersibility at the molecular scale.

[0050] S5. Cooling and Packaging: Cooled under an inert atmosphere and vacuum-sealed.

[0051] The calcined CaO was slowly cooled to below 200°C under nitrogen protection, and then vacuum-sealed (<100 Pa). Inert cooling prevented CaO from absorbing moisture or carbonizing during the cooling process, while vacuum sealing isolated it from moisture and carbon dioxide in the storage environment, ensuring the long-term dispersion stability of the final product.

[0052] Example

[0053] Example 1: Low template addition amount - high droplet diameter combination

[0054] S1: Precursor Preparation

[0055] Ca(OH)2 (purity 99.9%) and deionized water were mixed at a ratio of 1:9 (10wt%) and magnetically stirred (500rpm, 2h) to obtain a sol.

[0056] Add 5 wt% CNF (diameter 10-50 nm), continue stirring for 1 h, then add 0.05 wt% citric acid and sonicate (200 W, 30 min).

[0057] Droplets (40-50 μm in diameter) are generated by aerosol atomization (nozzle diameter 1.0 mm, pressure 0.2 MPa) and collected on a polytetrafluoroethylene plate.

[0058] S2: Template self-assembly

[0059] Nitrogen drying at 60℃ (flow rate 1L / min, 24h) forms a three-dimensional network structure.

[0060] S3: Gradient calcination

[0061] First stage: Increase the temperature to 400℃ at a rate of 1℃ / min and hold for 1 hour (nitrogen flow rate 3L / min).

[0062] Second stage: Increase the temperature to 700℃ at a rate of 10℃ / min and hold for 0.5h (nitrogen flow rate 5L / min).

[0063] S4: In-situ passivation

[0064] 0.3 vol% ethanol vapor (nitrogen carrier gas, total flow rate 5 L / min) was introduced at 700℃ and treated for 10 min.

[0065] S5: Cooling Encapsulation

[0066] Cooled to below 200°C by nitrogen gas, then vacuum sealed (pressure 100 Pa).

[0067] Example 2: High template addition amount - low droplet diameter combination

[0068] S1: Precursor Preparation

[0069] Ca(OH)2 (purity 99.9%) and deionized water were mixed at a ratio of 1:6 (15wt%) and magnetically stirred (800rpm, 2h) to obtain a sol.

[0070] Add 10wt% CNF (diameter 10-50nm), stir for 1h, then add 0.1wt% citric acid and sonicate (300W, 30min).

[0071] Droplets (10–20 μm in diameter) are generated by aerosol atomization (nozzle diameter 0.5 mm, pressure 0.5 MPa) and collected on a polytetrafluoroethylene plate.

[0072] S2: Template self-assembly

[0073] Nitrogen drying at 60℃ (flow rate 2L / min, 36h) forms a three-dimensional network structure.

[0074] S3: Gradient calcination

[0075] First stage: Increase the temperature to 400℃ at a rate of 2℃ / min and hold for 2 hours (nitrogen flow rate 5L / min).

[0076] Second stage: Increase the temperature to 700℃ at a rate of 15℃ / min and hold for 1 hour (nitrogen flow rate 8L / min).

[0077] S4: In-situ passivation

[0078] 0.7 vol% ethanol vapor (nitrogen carrier gas, total flow rate 8 L / min) was introduced at 700℃ and treated for 15 min.

[0079] S5: Cooling Encapsulation

[0080] Cooled to below 200°C with nitrogen and then vacuum sealed (pressure 50Pa).

[0081] Example 3: Median parameter combination - gradient rate enhancement

[0082] S1: Precursor Preparation

[0083] Ca(OH)2 (purity 99.9%) and deionized water were mixed at a ratio of 1:7 (12.5wt%) and magnetically stirred (600 rpm, 2 h) to obtain a sol.

[0084] Add 7.5wt% CNF (diameter 10-50nm), stir for 1h, then add 0.08wt% citric acid and sonicate (250W, 30min).

[0085] Droplets (25-35 μm in diameter) are generated by aerosol atomization (nozzle diameter 0.8 mm, pressure 0.3 MPa) and collected on a polytetrafluoroethylene plate.

[0086] S2: Template self-assembly

[0087] Nitrogen drying at 60℃ (flow rate 1.5L / min, 30h) forms a three-dimensional network structure.

[0088] S3: Gradient calcination

[0089] First stage: Heat to 400℃ at a rate of 1.5℃ / min and hold for 1.5h (nitrogen flow rate 4L / min).

[0090] Second stage: Heat to 700℃ at 12℃ / min and hold for 0.75h (nitrogen flow rate 6L / min).

[0091] S4: In-situ passivation

[0092] 0.5 vol% ethanol vapor (nitrogen carrier gas, total flow rate 6 L / min) was introduced at 700℃ and treated for 12 min.

[0093] S5: Cooling Encapsulation

[0094] Cooled to below 200°C with nitrogen and then vacuum sealed (pressure 75 Pa).

[0095] Comparative Example 1 (corresponding to Example 1: Removal of biological template)

[0096] The difference from Example 1 is that no cellulose nanofibers (CNF) are added, but the rest of the steps are exactly the same as in Example 1.

[0097] Validation objective: The necessity of biological templates for porous structures.

[0098] Comparative Example 2 (corresponding to Example 1: gradient calcination was cancelled)

[0099] The difference from Example 1 is that the staged temperature control calcination is cancelled, and the temperature is directly increased to 700°C at 10°C / min and held for 1.5 hours. The remaining steps are the same as in Example 1.

[0100] Verification objective: The effect of gradient calcination on porosity formation and grain size control.

[0101] Comparative Example 3 (corresponding to Example 2: Replacing the biological template)

[0102] The difference from Example 2 is that the cellulose nanofibers (CNF) are replaced with an equal amount of starch granules (50-100 μm in diameter), and the rest of the steps are the same as in Example 2.

[0103] Validation objective: The influence of biological template type on pore connectivity and size distribution.

[0104] Comparative Example 4 (corresponding to Example 2: in-situ passivation cancelled)

[0105] The difference from Example 2 is that no ethanol vapor passivation treatment is performed after calcination, and the remaining steps are the same as in Example 2.

[0106] Verification objective: The contribution of in-situ passivation to particle dispersibility and stability.

[0107] Comparative Example 5 (corresponding to Example 3: removal of dispersant)

[0108] The difference from Example 3 is that no citric acid dispersant is added, and the remaining steps are the same as in Example 3.

[0109] Validation objective: The effect of dispersants on precursor homogenization and droplet stability.

[0110] Comparative Example 6 (corresponding to Example 3: outside the calcination temperature range)

[0111] The difference from Example 3 is that the calcination temperature in the second stage is increased to 800°C (beyond the scope of the claims), while the remaining steps are the same as in Example 3.

[0112] Verification objective: The correlation between the upper limit of calcination temperature and grain size and purity.

[0113] Experiment Example 1: The Influence of Biological Templates on Pore Structure Experimental Description

[0114] Experimental steps

[0115] Sample preparation:

[0116] The calcined products of Examples 1-3 (containing CNF), Comparative Example 1 (without CNF), and Comparative Example 3 (starch replacing CNF) were selected, crushed, and sieved (100-150 mesh).

[0117] The sample was vacuum dried at 120℃ for 4 hours to remove adsorbed moisture.

[0118] Mercury porosimetry test:

[0119] Instrument: AutoPore IV 9500 mercury porosimeter (McMed Instruments, USA).

[0120] Parameter settings:

[0121] Pressure range: 0.1-60000psi (corresponding to pore size 0.003-360μm).

[0122] Mercury contact angle: 130°, surface tension: 485mN / m.

[0123] Data collection point: Volume change is recorded every 10 psi.

[0124] Operating procedures:

[0125] Weigh 0.5g of the sample and put it into the dilatometer.

[0126] Detect large pores (>1μm) during the low-pressure stage (0.1-30psi).

[0127] High-pressure stage (30-60000psi) detection of mesopores / micropores (<1μm).

[0128] Clean the sample and calculate the porosity and pore size distribution.

[0129] Data processing:

[0130] Total porosity (%) = (volume of mercury indented / apparent volume of sample) × 100%.

[0131] The average pore size is taken as the peak value of the distribution curve, and the pore density (pores / mm²) is taken as the average pore size. 2 )Calculated using the BJH model.

[0132] Permeability score: The score is determined by a combination of the peak width of the pore size distribution and the mercury increment ratio in the low-pressure / high-pressure stages (1-5 points, with 5 points being the best).

[0133]

[0134]

[0135] Table 1. Test data on the effect of biological templates on the pore structure of calcium oxide.

[0136] In this process, bio-templates (cellulose nanofibers, CNFs) achieve precise control over the pore structure of calcium oxide through a multi-scale synergistic mechanism. The nanofiber properties of CNFs allow them to disperse uniformly in the precursor sol and form a three-dimensional interwoven network with calcium source particles via hydrogen bonding. During the low-temperature drying stage, this network is fixed into a rigid framework through dynamic hydrogen bonding, providing directional channels for subsequent calcination and pore formation. During gradient calcination, CNFs preferentially pyrolyze at low temperatures below 400℃, releasing CO / H2O gases that escape along the pre-formed network channels, thereby generating a porous structure with a concentrated pore size distribution (1-5 μm) and good interconnectivity. Comparative Example 1 (without CNF) lacked template guidance, resulting in random gas escape paths and a significant decrease in porosity (29.8%), with isolated micropores predominating. In contrast, Comparative Example 3 (starch replacing CNF) exhibited a different pattern due to the micron-sized starch particles and their high-temperature decomposition characteristics (>500℃). The pyrolysis of starch particles lagged behind that of the calcium source, and the framework partially collapsed during gas release, ultimately forming discrete macropores (5.6 μm) and a low-connectivity structure, further demonstrating the irreplaceability of CNF.

[0137] In this process, the precise matching of the nanoscale effect and thermal response behavior of CNF is the core of pore structure optimization. The diameter of CNF (10-50 nm) and the size of calcium source particles (submicron level) complement each other, and the uniform composite of the two within micron-sized droplets is achieved through the droplet confinement effect of aerosol atomization. This cross-scale composite structure exhibits hierarchical decomposition characteristics during the calcination stage: the low-temperature decomposition of CNF (200-400℃) preferentially creates pores, while the high-temperature decomposition of the calcium source (500-700℃) generates calcium oxide grains within the already formed pore framework, avoiding the temporal conflict between pore formation and crystal formation in traditional processes. The test data of Comparative Example 2 (without gradient calcination) show that single high-temperature calcination leads to the simultaneous decomposition of CNF and calcium source, with gas release and grain growth interfering with each other, ultimately causing pore collapse and grain coarsening, which in turn verifies the scientific nature of the staged temperature control in this process.

[0138] Furthermore, CNF's bio-derived nature provides an advantage in greening the process. Its fully decomposable nature (no ash residue) combined with the volatility of the ethanol passivating agent ensures high purity (>99.8%) of the final product. In contrast, the test results for Comparative Example 3 (starch template) show that although starch can achieve partial pore formation, the carbon residue from its incomplete decomposition (0.3-0.5 wt% residual carbon detected) significantly reduces the purity of calcium oxide, and micron-sized starch particles cannot replicate the nano-confining effect of CNF. This comparison reveals the unique value of CNF in achieving a synergistic improvement in lightweight, high purity, and environmental friendliness.

[0139] Experiment Example 2: Effect of Gradient Calcination on Grain Size - Experimental Description

[0140] Experimental steps

[0141] Sample preparation:

[0142] Take the calcium oxide products from Examples 1-3 (gradient calcination), Comparative Example 2 (gradient calcination cancelled), and Comparative Example 6 (calcination at 800℃) and grind them to below 200 mesh.

[0143] Store the sample in a desiccator (humidity < 10% RH) for 24 hours to avoid moisture absorption.

[0144] X-ray diffraction (XRD) test:

[0145] Instrument: Bruker D8 Advance diffractometer (Cu-Kα radiation, ).

[0146] Parameter settings:

[0147] Scan range: 20-80° (2θ), step size 0.02°, scan speed 2° / min.

[0148] Voltage / Current: 40kV / 40mA.

[0149] Operating procedures:

[0150] Take 0.5g of sample and spread it evenly on the glass sample stage.

[0151] XRD patterns were collected, and characteristic peaks of CaO (2θ = 32.2°, 37.4°, 53.9°) were marked.

[0152] The grain size is calculated using the Scherrer formula: D = Kλ / (βcosθ) (K = 0.89, β is the full width at half maximum).

[0153] Transmission electron microscopy (TEM) verification:

[0154] Instrument: JEOL JEM-2100F field emission transmission electron microscope.

[0155] Sample preparation: The powder was ultrasonically dispersed in ethanol and then dropped onto a copper mesh carbon film.

[0156] Observation parameters: accelerating voltage 200kV, 10 fields of view were selected to statistically analyze grain size distribution.

[0157] Crystal form integrity analysis:

[0158] The XRD data were refined using Jade software with Rietveld refinement, and the lattice distortion rate and crystal integrity score (0-100%) were calculated.

[0159] Example 1 34.2±1.8 30-45 94.3 Example 2 28.7±2.1 25-38 96.8 Example 3 31.5±1.5 28-42 95.1 Comparative Example 2 82.6±4.3 70-110 76.5 Comparative Example 6 128.9±6.7 100-160 63.2

[0160] Table 2. Test data on the effect of gradient calcination on calcium oxide grain size.

[0161] The phased temperature control design of gradient calcination achieves precise control of grain size by decoupling the decomposition of the biotemplate and the crystallization process of the calcium source in a temporal sequence. In the first stage (200-400℃), the biotemplate (CNF) preferentially pyrolyzes to generate CO2 / H2O gas. Its dynamic release not only forms interconnected pores but also creates a local high-pressure microenvironment around the calcium source particles. In the second stage (500-700℃), when the calcium source rapidly decomposes into calcium oxide crystal nuclei, the diffusion resistance of the residual gas significantly inhibits the Ostwald ripening of the grains, thus limiting the grain size to below 50nm. The grain coarsening (82.6nm) in Comparative Example 2 (without gradient calcination) shows that the simultaneous decomposition of the template and the calcium source under a single high temperature condition leads to mutual interference between gas release and grain growth, while overtemperature calcination (Comparative Example 6, 800℃) causes severe sintering (128.9nm) due to the reduction of the grain boundary migration barrier, which inversely verifies the irreplaceable nature of phased temperature control.

[0162] In this process, the second-stage calcination with rapid heating (10-15℃ / min) further enhances grain size control. The design of short-term holding at high temperature (0.5-1h) shortens the grain diffusion time window, while the forced convection of the nitrogen atmosphere (5-8L / min) accelerates the discharge of pyrolysis gases, avoiding local overpressure collapse caused by their retention. This synergistic effect of thermodynamics and kinetics results in the smallest grain size (28.7nm) and the highest crystal integrity (96.8%) in Example 2 (heating rate 15℃ / min). In contrast, Comparative Example 6 (calcination at 800℃) exceeded the critical temperature for calcium source decomposition, leading to lattice distortion (peak shift of 0.3°) and surface sintering, confirming the scientific validity of the upper temperature limit setting.

[0163] From an energy efficiency perspective, the low-temperature-high-temperature segmented strategy of gradient calcination significantly reduces energy consumption compared to the traditional single high-temperature process (>1200℃). The pyrolysis of the bio-template in the low-temperature stage can partially compensate for the endothermic demand of calcium source decomposition, reducing overall energy consumption by about 40% and reducing CO2 emissions (>60%). However, the test data of Comparative Example 2 (crystal integrity 76.5%) shows that even at the same maximum temperature (700℃), the lack of segmented temperature control still leads to low energy utilization efficiency and accumulation of grain defects.

[0164] Experiment Example 3: Effect of In-situ Passivation on Dispersion and Stability (Experimental Description)

[0165] Experimental steps

[0166] Sample pretreatment:

[0167] Take calcium oxide samples from Examples 1-3 (passivated with ethanol vapor) and Comparative Example 4 (without passivation) and place them in a drying oven (60℃, 24h) to remove adsorbed moisture.

[0168] The samples were dispensed into sealed glass bottles, labeled, and stored in a 25℃ / 50%RH constant temperature and humidity chamber for later use.

[0169] Dispersion test (laser particle size analyzer):

[0170] Instrument: Malvern Mastersizer 3000 laser particle size analyzer (dry injection).

[0171] Parameter settings:

[0172] Dispersion pressure: 2 bar, measurement range 0.01-3500 μm.

[0173] Light blocking range: 5-15%, average value of 3 scans.

[0174] Operating procedures:

[0175] Take 0.1g of sample and add it to the dry injection cell, then disperse it with compressed air.

[0176] Record the D10, D50, D90 values ​​and the dispersion index (PDI).

[0177] Stability testing (hygroscopicity analysis):

[0178] Instrument: Dynamic Moisture Adsorption Analyzer (DVSAdvantage).

[0179] Parameter settings:

[0180] Humidity gradient: 0%RH → 50%RH (step size 10%RH, equilibration time 2h per step).

[0181] Temperature: 25℃, sample volume: 10mg.

[0182] Data acquisition: Record the moisture absorption weight gain curve and equilibrium time.

[0183] Surface chemical analysis (XPS):

[0184] Instrument: Thermo Scientific K-Alpha X-ray photoelectron spectrometer.

[0185] Test conditions:

[0186] Excitation source: Al-Kα (1486.6 eV), beam size 400 μm.

[0187] Binding energy correction: based on C1 s (284.8 eV).

[0188] Analysis objective: To detect the intensity ratio of characteristic peaks of surface hydroxyl (-OH) and passivation layer (COC).

[0189]

[0190] Table 3. Test data on the effect of in-situ passivation on the dispersibility and stability of calcium oxide.

[0191] In-situ passivation technology constructs a dense hydroxylated protective layer on the surface of calcium oxide through a high-temperature gas-solid reaction, fundamentally suppressing the tendency of particles to absorb moisture and agglomerate. At the end of calcination (700℃), ethanol vapor undergoes a dehydrogenation condensation reaction with the highly active CaO surface, generating a network of chemically bonded hydroxyl (-OH) and ether (COC) bonds. This passivation layer significantly improves the dispersion stability of the particles (D90 < 200 nm) by reducing surface energy (XPS shows hydroxyl coverage > 88%) and physically shielding water molecule adsorption sites. Comparative Example 4 (no passivation) test data (D90 = 532 nm, moisture absorption 18.6%) shows that the unpassivated CaO surface, due to a large amount of unsaturated Ca... 2+ When exposed, it readily adsorbs H2O and CO2 from the environment, causing uncontrollable particle aggregation and volume expansion, which in turn verifies the necessity of the passivation layer in regulating surface activity.

[0192] From a kinetic perspective, the advantage of high-temperature passivation lies in the controllability of its reaction rate. Ethanol vapor decomposes into active free radicals (·CH2CH2O) at 700°C. These free radicals rapidly combine with oxygen vacancies on the CaO surface to form a uniform molecular-level passivation layer. Compared to traditional post-processing coatings (such as wet coating with silane coupling agents), this process avoids the problems of solvent residue and uneven passivation caused by multilayer stacking (TEM shows that the agglomeration rate in the examples is <15%). Simultaneously, the thermal stability of the hydroxylation layer (>300°C) ensures the long-term reliability of the final product during subsequent processing or storage, while traditional physical coating layers (such as stearic acid) are prone to decomposition and failure at high temperatures.

[0193] Furthermore, the chemical bonding mechanism between the passivation layer and the calcium oxide matrix endows the material with environmentally adaptive properties. In environments with fluctuating humidity (e.g., 50% RH), the ether bonds (COC) in the passivation layer can reversibly combine with a small amount of adsorbed water through hydrogen bonding to form a dynamic protective film (hygroscopicity <3.7%). This prevents water molecules from penetrating the matrix and avoids secondary aggregation caused by the passivation layer itself due to swelling and shedding. This characteristic is difficult to achieve in traditional passivation processes—the hygroscopicity of Comparative Example 4 (18.6%) and TEM observation results (85% aggregation) indicate that simple physical isolation or low-temperature passivation cannot cope with complex environmental stresses. This process, through the synergistic design of interface chemistry and reaction engineering, overcomes the common technical bottleneck of the difficulty in stably dispersing highly reactive metal oxides.

[0194] Experiment Example 4: Effect of Dispersants on Precursor Homogenization - Experimental Description

[0195] Experimental steps

[0196] Precursor droplet solidification:

[0197] Uncalcined precursor droplets from Examples 1-3 (containing 0.05-0.1 wt% citric acid) and Comparative Example 5 (without citric acid) were rapidly frozen (quickly cooled with liquid nitrogen, -196°C) and then freeze-dried (-50°C, 24h) to preserve the original morphology of the droplets.

[0198] Scanning electron microscopy (SEM) and element mapping:

[0199] Instrument: Hitachi SU8010 field emission scanning electron microscope, equipped with Oxford EDS detector.

[0200] Parameter settings:

[0201] Acceleration voltage: 5kV, working distance: 8mm.

[0202] Elemental analysis: Ca-Kα (3.69 keV) and C-Kα (0.28 keV) line scans and surface distributions.

[0203] Operating procedures:

[0204] The freeze-dried sample was sputter-coated with gold (5nm thickness) and fixed onto conductive adhesive.

[0205] Select a cross-sectional region from the center to the edge of the droplet and acquire images of secondary electrons (SE) and backscattered electrons (BSE).

[0206] For the selected region (50×50μm) 2 Perform surface distribution scans of Ca and C elements (step size 0.1 μm).

[0207] Image analysis and homogenization scoring:

[0208] The coefficient of variation (CV) of the Ca / C element distribution was calculated using ImageJ software: CV = (standard deviation / mean) × 100%.

[0209] Homogeneous scoring (0-100%): Calculated based on CV value weighting (CV < 10% is scored as 100%, and 10 points are deducted for every 5% increase in CV).

[0210] Statistical analysis of droplet diameter and particle distribution:

[0211] Fifty droplets were randomly selected, their diameters were measured, and the coefficient of variation (droplet diameter consistency) was calculated.

[0212] Particle aggregation density (number of bright spots per unit area) was calculated using BSE image grayscale analysis.

[0213]

[0214] Table 4. Test data on the effect of dispersants on precursor homogenization

[0215] Citric acid dispersant achieves nanoscale homogenization and composite formation of calcium source and biological template (CNF) within precursor droplets through multiple interaction mechanisms. The carboxylic acid groups (-COOH) in the citric acid molecule interact with the Ca2+ groups on the surface of the calcium source particles. 2 Specific coordination occurs, forming a charged adsorption layer whose electrostatic repulsion effectively inhibits van der Waals aggregation between particles. Simultaneously, the hydroxyl groups (-OH) at the ends of citric acid molecules are bridged with the cellulose chains of CNF via hydrogen bonds, constructing an interpenetrating network structure of calcium source-CNF. This synergistic chemical-physical dispersion mechanism is enhanced during aerosol atomization—the shear force generated by high-speed atomization promotes dynamic adsorption-dissociation of citric acid molecules, continuously maintaining the uniform distribution of components within the droplet (Ca element CV < 9%). In contrast, the test data of Comparative Example 5 (without dispersant) (CV > 23.6%) indicates that the lack of such regulation leads to component migration and local segregation during droplet drying.

[0216] From the perspective of droplet solidification kinetics, the introduction of dispersants significantly optimizes mass transfer behavior during the drying process. In the freeze-drying stage, citric acid-Ca... 2 The high stability of the coordination complex suppressed capillary aggregation induced by water evaporation, allowing the three-dimensional interwoven structure of CNF and calcium source to be fully preserved (SEM showed that the droplet diameter variation coefficient of the example was <6.5%). In contrast, the droplets of Comparative Example 5 formed obvious size dispersion (variance coefficient 18.7%) and particle-rich regions (aggregation density 7.6 particles / μm) during drying due to uneven internal component migration resistance. 2 This difference reveals the crucial role of dispersants in bridging the mass transfer barriers at the micron to nanoscale: their molecular-level interface modification capabilities can simultaneously regulate interparticle forces and interfacial energies, thereby breaking through the homogenization limits of traditional mechanical stirring.

[0217] Furthermore, the thermal response characteristics of citric acid are closely related to the sustainability of the process. In the subsequent calcination stage (200-400℃), citric acid molecules preferentially decompose into CO2 and H2O, with negligible residual ash (<0.01wt%), avoiding the purity reduction problem caused by high-temperature carbonization of traditional dispersants (such as polyvinyl alcohol). The pore defects (incompletely decomposed aggregates) observed in the SEM image of Comparative Example 5 indicate that precursors lacking dispersants are prone to structural stress concentration during calcination due to uneven composition, thus verifying the necessity of homogeneous dispersion for the structural integrity of the final product. This process combines the function and environmental friendliness of dispersants through molecular design, achieving controllable dispersion throughout the entire process from droplets to the final product, providing a new paradigm for the controllable preparation of highly reactive materials.

[0218] Test Example 5: Effect of Calcination Temperature on Product Purity - Experimental Description

[0219] Experimental steps

[0220] Sample preparation:

[0221] Take the calcium oxide products from Examples 1-3 (calcined at 700℃) and Comparative Example 6 (calcined at 800℃) and grind them to below 200 mesh.

[0222] The sample was ultrasonically cleaned in 10% hydrochloric acid for 5 minutes (to remove surface adsorbed impurities), rinsed with deionized water until neutral, and dried at 120°C for 2 hours.

[0223] Purity analysis (ICP-MS):

[0224] Instrument: Agilent 7900 inductively coupled plasma mass spectrometer.

[0225] Parameter settings:

[0226] RF power: 1550W, sampling depth: 8mm.

[0227] - Internal standard elements: 115In, 103Rh (concentration 10ppb).

[0228] Operating procedures:

[0229] Weigh 0.1g of the sample and digest it with 5mL of HNO3 (65%) using microwave (200℃, 30min), then bring the volume to 50mL.

[0230] The content of impurity elements (Fe, Al, Si, Mg, etc.) is detected, and the purity of CaO is calculated: Purity (%) = 100% - Σ (impurity content).

[0231] Residual carbon detection (elemental analyzer):

[0232] Instrument: Elementarvario ELCube elemental analyzer.

[0233] Parameter settings: Combustion temperature: 1150℃, Carrier gas: Helium (flow rate 200mL / min).

[0234] Operating procedures:

[0235] Weigh 10mg of sample, wrap it in tin foil, and put it into the combustion tube.

[0236] Detect the CO2 release and calculate the residual carbon content (wt%).

[0237] Phase analysis (XRD):

[0238] Instrument: RigakuSmartLab diffractometer (Cu-Kα radiation).

[0239] Parameter settings: Scan range 10-80° (2θ), step size 0.02°.

[0240] Analysis objective: To detect characteristic peaks of impurity phases such as CaCO3 and CaOH2.

[0241]

[0242]

[0243] Table 5. Test data on the effect of calcination temperature on the purity of calcium oxide.

[0244] The choice of calcination temperature determines the purity and chemical stability of the final product by regulating the balance between the decomposition kinetics of the biotemplate and the lattice stability of calcium oxide. At the optimized temperature of 700℃, the biotemplate (CNF) and citric acid dispersant fully pyrolyze into CO2 and H2O in the low-temperature stage (200-500℃), and their rapid dissipation avoids carbon residue (residual carbon <0.11% in the example); while the CaO crystals generated by the decomposition of the calcium source reach a thermodynamically stable state at this temperature, the surface energy is reduced to a minimum, and the re-reaction with CO2 / H2O in the environment is effectively suppressed (no impurity phase detected). In contrast, the calcination at 800℃ in Comparative Example 6 resulted in a double negative effect: on the one hand, the overheating caused trace corrosion of the Al2O3 crucible (Al impurities 85ppm) and increased the oxygen vacancy concentration in the CaO lattice, exacerbating the chemisorption of CO2 (generating 1.2% CaCO3); on the other hand, the grain boundary migration rate accelerated at high temperature, leading to abnormal grain growth (XRD peak width narrowing), exposing more active sites, which then combined with water molecules to generate Ca(OH)2 (0.8%).

[0245] In this process, the synergistic design of the upper temperature limit and the gas atmosphere further ensures the controllability of purity. Nitrogen protection (5 L / min) continuously vents pyrolysis gases during the calcination stage at 700℃, blocking their secondary reaction pathway with CaO; while the gradient heating strategy (10℃ / min) slows down the decomposition rate of the calcium source, ensuring that the decomposition products of CNF and citric acid are completely discharged from the system before CaO crystal nuclei form. This spatiotemporal separation mechanism enables the CaO purity of the example to exceed 99.7%, and the lattice distortion rate to be less than 0.5%. In contrast, in Comparative Example 6, a single rapid heating (20℃ / min) causes pyrolysis gases to remain, and some of the unreleased CO2 rebonds with CaO in the high-temperature region, forming bulk carbonate inclusions (SEM shows submicron-sized pores), which in turn verifies the necessity of using gradient temperature control and atmosphere in combination.

[0246] From the perspective of energy efficiency and sustainability, the mild calcination conditions at 700℃ show significant advantages compared to traditional high-temperature processes (>1000℃). The heat release from the low-temperature decomposition of the bio-template can compensate for the endothermic demand of calcium source decomposition, reducing overall energy consumption by approximately 35%. Simultaneously, the closed-loop design with a nitrogen atmosphere reduces protective gas consumption (saving 60%). However, the test data from Comparative Example 6 (purity 98.1%) indicates that even under the same equipment conditions, simply increasing the temperature not only fails to improve purity but also increases overall costs due to side reactions and equipment wear and tear.

[0247] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A process for modifying high-purity calcium oxide with light and highly dispersed properties, characterized in that: Includes the following steps: S1. Precursor preparation: Calcium source, biological template and dispersant are mixed to form a sol, which is then atomized into droplets by aerosol; In step S1: The droplet diameter of aerosol atomization is 10–50 μm; The biological template is cellulose nanofiber, and the amount added is 5-10 wt% of the dry weight of the calcium source; Citric acid is used as the dispersant, and its addition amount is 0.05–0.1 wt% of the dry weight of the calcium source. S2, Template self-assembly: The droplets are dried at low temperature, allowing the biological template and calcium source to assemble into a three-dimensional network structure; S3, gradient calcination: staged temperature-controlled calcination, the first stage decomposes the biological template to generate pores, the second stage decomposes the calcium source to generate calcium oxide; In step S3: The first stage of calcination is at a temperature of 200–400℃, with a heating rate of 1–2℃ / min, and is held for 1–2 hours. The second stage of calcination is carried out at a temperature of 500–700℃, with a heating rate of 10–15℃ / min and a holding time of 0.5–1 hour. S4. In-situ passivation: Passivating agent vapor is introduced at the end of the calcination stage to modify the surface of calcium oxide; S5. Cooling and Packaging: Cooled under an inert atmosphere and vacuum-sealed.

2. The process for modifying high-purity calcium oxide with light and highly dispersed materials according to claim 1, characterized in that, In step S2: The low-temperature drying temperature is 60±2℃, the drying atmosphere is nitrogen, and the flow rate is 1~2L / min; The self-assembly is achieved through hydrogen bonding, forming through-pores with a diameter of 1–5 μm.

3. The process for modifying high-purity calcium oxide with light and highly dispersed materials according to claim 1, characterized in that, The second stage of calcination is carried out under a nitrogen atmosphere with a gas flow rate of 5–8 L / min.

4. The process for modifying high-purity calcium oxide with light and highly dispersed materials according to claim 1, characterized in that, In step S4: The passivating agent is ethanol vapor with a concentration of 0.3–0.7 vol%. The passivation treatment temperature is 650-700℃, and the treatment time is 10-15 minutes.

5. The process for modifying high-purity calcium oxide with light and highly dispersed materials according to claim 1, characterized in that, In step S5: Cooling was carried out under a nitrogen atmosphere at a flow rate of 3–5 L / min, with a final cooling temperature of <200℃. The vacuum level of the vacuum seal is <100Pa.

6. The process for modifying high-purity calcium oxide with light and highly dispersed materials according to claim 1, characterized in that, The matching relationship between the droplet diameter of 10-50 μm and the amount of biological template added of 5-10 wt% satisfies the following: the ratio of droplet volume to template network volume is 1:0.2-0.

5.

7. The process for modifying high-purity calcium oxide with light and highly dispersed materials according to claim 1, characterized in that, The ratio of the heating rate of the first stage calcination (1-2℃ / min) to the heating rate of the second stage calcination (10-15℃ / min) is 1:5 to 1:

10.

8. The process for modifying high-purity calcium oxide with light and highly dispersed materials according to claim 4, characterized in that, The correlation between the ethanol vapor concentration of 0.3–0.7 vol% and the passivation temperature of 650–700 °C satisfies the following condition: for every 0.1 vol% increase in ethanol vapor concentration, the passivation temperature decreases by 10–15 °C.

Citation Information

Patent Citations

  • Preparation method of superfine light calcium carbonate

    CN115448346A

  • Anti-oxidation copper powder, preparation method and application thereof

    CN118527652A